“Isolamento, caracterização bioquímica e potencial de Trichoderma spp. para promoção de crescimento da soja” - Rodrigo Mattos Silva Galeano (2024)
In the agricultural soils of the Brazilian Cerrado, the nutrient content is significantly low, leading many farmers to frequently apply fertilizers. However, the recent fertilizer crisis has driven the search for more sustainable and economical alternatives for agricultural management. Bio-inputs based on Trichoderma are able to increase the availability of nutrients for plants and protect them from attack by phytopathogens. In addition, these fungi can improve soil quality by colonizing the rhizosphere, increasing the activity of enzymes involved in biogeochemical processes. Therefore, the aim of this study was to select, characterize and evaluate the effect of inoculation of new Trichoderma spp. isolates on soybean growth and productivity. The fungi were isolated from the rhizospheric soil of soybean plants grown in São Gabriel do Oeste, MS, Brazil. The isolates were tested against soybean crop pathogens, and the three isolates chosen were characterized for their plant growth-promoting mechanisms, tolerance to different conditions and agrochemicals. Theisolates were then inoculated into soybean seeds (cv. Nidera NS6601), and their effect on germination and initial development was determined. The effect of inoculation of the isolates on productivity was assessed in field experiments using two cultivars of soybean (Nidera NS6601 and DM 69IX60RSF 12X RR2 PRO), and two doses of phosphate fertilization (400 and 200 kg ha-1) of simple superphosphate (SSP). After 48 days of planting, samples were collected for leaf analysis and evaluation of the enzymatic activities of the rhizospheric soil of the plants .Of the 66 Trichoderma spp. isolates obtained, GT-8 (T. viride), GT-31 (T. reesei), and GT-32 (T. longibrachiatum) were selected. They showed various plant growth-promoting abilities in vitro, including indole-3-acetic acid production, phosphate solubilization, siderophore synthesis, as well as tolerance to adverse conditions and growth in media with different agrochemicals. They did not inhibit seed germination and significantly promoted seedling growth, with a notable increase in the shoot and root of the plants, especially when co-inoculated, increasing by 50.3% and 48.8% respectively. In the field, GT-32 inoculation (200 kg ha-1) on soybeans (cv. Nidera NS6601) resulted in a 4.3% increase in grain yield. While for the cv. DM 69IX60RSF 12X RR2 PRO, the use of GT-31 and GT-32 at half the fertilizer dose resulted in yield increases of 22.7% and 18.6%, respectively, compared to the control. Inoculated plants showed a higher content of chlorophylls, phenolic compounds, flavonoids and antioxidant responses in both fertilization conditions, with higher activities of the enzymes catalase, peroxidase and ascorbate peroxidase. Moreover, the enzyme activities were higher in the rhizospheric soil of inoculated soybean plants. The findings of this study demonstrated the potential of new Trichoderma strains to increase soybean growth and productivity, and minimize the use of fertilizers in the field. Finally, the use of these new strains could also be a sustainable strategy to improve soil health and fertility.